Peran Kemandirian Belajar dan Konsep Diri pada Hasil Belajar IPS - Rani Puspita Sari; Zulela Zulela; Yunita Sari; Siti Nurhayati; Rasmita Rasmita (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This research aims to determine the correlation between self-regulated learning and self-concept of students with the results of Social Study. The research method used was a survey using regression analysis, simple correlation, and multiple regression and correlation. The research was conducted in SDN Pondok Kopi 08 Pagi, District of Duren Sawit, East Jakarta, with n = 91 using cluster random sampling technique. The results showed that: (1) there is a positive correlation between self-regulated learning with learning outcomes of Social Study; (2) there is a positive correlation between self-concept of students with learning outcomes of Social Study; (3) there is a positive correlation between self-regulated learning and self-concept of students together with the results of Social Study. Based on the research results, the learning outcomes of Social Study can be improved by increasing self-regulated learning and self-concept of the students, because the results of the verification prove that self-regulated learning and self-concept of students are significant determinants. Keywords: Self-Regulated Learning, Self-Concept, Learning Outcome of Social Study